Tradition/Modernity: Weaving and dyeing initiatives in Jaffna - Sanathanan, T. (My University, 2022)
Existing museum and private collections of dyed cotton cloths and written documents reveals that Jaffna peninsula had a history of flourishing weaving industry under the local kings and Dutch colonial rule intertwine with the histories of migration, caste system, colonial networks and slavery. The local dyeing and weaving reached a complete collapse with the introduction of chemical dyes and imported cloths during the British administration. Later in 19 thcentury colonial and national governments’ initiatives to revive the local industry connected weaving with economic development of the country, especially of the women of the underprivileged sections of the society. In Jaffna, the involvement of American Christian Mission in setting up of handlooms among the new converts ignited a new religious competition between Christians and Saivates in the field. Further, Mahatma Gandhi’s visit in 1928 to Jaffna brought a Swadeshi political dimension to weaving. These developments have configured the social dynamics of traditional weaving and dyeing in Jaffna. Later the government of Sri Lanka’s attempts to establish weaving schools all over the island brought this craft under uniform syllabi by erasing the regional variations in materials, methods and designs. In this context this paper unpacks the meaning and the politics of a new endeavor in natural dying and handloom weaving known as “Kolam’’, by a group of artists and university graduates, started in February 2017, with the objective of archiving traditional knowledge through practice, collaboration with artists and craft persons, and cater to the need of contemporary fashion and tourist industry. This paper attempts to read how Kolam’s initiative negotiates with existing binaries such as art and craft, tradition and modern, past and present, and function and aesthetics.